La electrónica de potencia aplicada a un generador de plasma térmico - Pacheco, Joel; Olea, Oscar; Andrade, Roberto; Silva, Javier; Martínez, Gabriel (CIENCIA ergo-sum; Vol. 3 Núm. 1 (1996): CIENCIA ergo-sum (marzo-junio 1996), 2017)
-